A prospective pilot study to evaluate an animated home-based physical exercise program as a treatment option for patients with rheumatoid arthritis. Issue 1 (December 2016) - Zernicke, Jan; Kedor, Claudia; Müller, Angela; Burmester, Gerd-Rüdiger; Reißhauer, Anett; Feist, Eugen
Abstract Background Physical exercises and physiotherapy are of great importance for maintenance of joint function in patients with rheumatoid arthritis (RA). However, many RA patients complain about problems to receive prescriptions or have a lack of access to physiotherapy. Recent reports have shown positive effects of the Wii game console on physical and psychosocial conditions of patients with other underlying diseases. The primary objectives of this prospective controlled pilot study were to investigate feasibility and patients' assessment using an animated home-based exercise program. Method This pilot study was conducted as a single-center, cross-over trial with two treatment arms over 24 weeks. Eligibility criteria included patients with RA reaching low disease activity under therapy with a biological disease modifying anti-rheumatic drug (bDMARD). After detailed instruction, 15 patients started with a conventional home-based physical exercise program and 15 patients began with a predefined animated exercise program by using the Wii game console for 12 weeks. Afterwards, patients were crossed-over to the other treatment arm for another period of 12 weeks. Multi-methodical assessments were performed by qualitative analysis of the interview-data as well as statistical analysis of functional tests and patient reported outcomes (PRO's). Results Evaluation of the interviews indicated feasibility and usefulness of the chosen animated home-based exercise program. Forefoot disabilities were identified as a main limiting factor for performing some of the animated exercises. After 12 weeks, both treatment arms showed improvement of functional tests without significant differences between groups: Overall muscle strength improved for a mean value of 10 Newton (+12 %) and the mean 6-min walk test (6-MWT) distance increased for 28 meters (+5 %). Conclusion This study showed that an animated home-based exercise program by using a Wii game console was feasible and beneficial for RA patients. Compared to standard physical home exercises, similar effects were observed indicating that such an animated program might be an alternative supportive option for RA patients. Trial registration ClinicalTrials.gov ID:NCT02658370 (19-Jan-2016).